Simetri dalam Desain: Aplikasi Web untuk Pembangkitan Motif Karpet Turki Berdasarkan Grup Frieze dan Kristalografi: Penelitian - Cindy Injilia S; Muthia Shafa Nazahra; Septika Aulia Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research develops a web-based application named Symmetry Studio for the generation of Turkish carpet motifs based on the principles of Group Frieze and Crystallography. This research addresses the need for a digital tool that integrates the concept of mathematical symmetry with traditional carpet design. Using research and development (R&D) methodology, the application was built with HTML, CSS, JavaScript, and p5.js library for real-time visualization. The application has interactive features including pattern type selection (frieze, crystallography, or mixed), 21 motif styles (flower, star, spiral, geometric pattern, etc.), various symmetry transformations (translation, reflection, rotation, shear reflection, etc.), and customizable color settings. Results show that the application successfully generates aesthetically pleasing Turkish carpet motifs through mathematical transformations, producing three different types of patterns: Frieze patterns for border designs, Crystallographic patterns for the main surface of the carpet, and mixed patterns for dynamic ornamental effects. The web-based platform provides accessibility through GitHub Pages, enabling widespread use in education, research, and creative industries. This research contributes to the preservation and innovation of traditional carpet design while strengthening the integration of math, art, and technology in digital design methodologies.